(untitled) (Bioscience Journal, 2018)
The increase in life expectancy occurred along an increase in the demand of edentulous patients for a type of rehabilitation that provides higher masticatory efficiency. Thus, implant overdentures using the ball/o-ring and bar-clip attachment systems represent a muco-supported and implant-retained prosthetic type that allows greater security, stability, and aesthetics, besides presenting a lower cost and easier hygiene. The present study aims to report a clinical case of overdenture with the o-ring retention system. In this case, the patient complained of difficulties during mastication due to instability of the mandibular complete denture, sensitivity from the superficialization of the mental foramina, dissatisfaction with aesthetics, and successive dislocations of the mandibular condyle. After clinical and radiographic evaluation, the treatment proposed was the installation of two osseointegrated implants between the mental foramina and the o-ring attachment overdenture. This prosthetic rehabilitation presents a successful clinical follow-up of 24 months, confirming the effectiveness of the treatment applied. The patient was satisfied because the implant-retained prosthesis provided benefits related to aesthetics, comfort, phonation, and mastication. It is noted that the rehabilitation performed has solved the patient’s initial complaints. After the clinical case and literature review, it is concluded that overdentures using the o-ring retention system are viable alternatives and provide adequate function and aesthetics, presenting integration with the stomatognathic system.